PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD(STUDENT TEAMS ACHIEVEMENT DIVISION) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SD NEGERI 19 MUARA DUA KECAMATAN SIAK KECIL KABUPATEN BENGKALIS - Isniarni Isniarni; Lazim.N Lazim.N; Otang kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The research carried out base on the lowly of the result of IPA in grade IIIth SDN 19 Muara dua which is about 60,5 within minimal completeness criterion stated is 65. Among 20 student, there was only 5 students were able to achieve the score of minimal completeness criterion stated. The purpose of this research is to improve student’s achievemet on IPA of the three graders in SDN 19 Muara dua with the application of STAD (Student Teams Achievement Devision).. This research was classroom action research consisting 2 cycles within 4 procedures : planning, doing, observing, and reflecting and each cycle consist of three meeting. Instruments on this research are syllabus, lesson plan, and student work sheet. Instrument for collecting data are observation sheet and test. Data which was collected were learning outcomes and teacher’s activities during lessons. After implementation of STAD (Student Teams Achievement Devision) model. it was abtained student’s outcomes in UH I within average 70,25(improved from basic score 16,11%). The average score form UH II was 78,75(improved 30,16%). Teachers activities results in the first meeting of the first cycle was 66,6% (good category), and then 75% (good category) for the second meeting in cycle I. Meanwhile in the first meeting of the second cycle was 83,33% (very good category) and then 87,5% (very good category) for second meeting in cycle II. Students activity in the first meeting of the cycle I was 62,5% (good category), 75% (good category) for the second meeting in the cycle I. And then in the first meeting of the second cycle was 79,1% (good category), 87,5% (very good category) for the second meeting in cycle II. Based on the result it can be concluded that implementation ofSTAD (Student Teams Achievement Devision)model can IPA in three graders at SDN 19 Muara dua Kecamatan Siak Kecil Kabupaten BengkalisKeywords : STAD (Student Teams Achievement Devision), Students Achievement the Result